Dual stage approach to laser-driven helical coil proton acceleration - S Ferguson; P Martin; H Ahmed; E Aktan; M Alanazi; M Cerchez; D Doria; J S Green; B Greenwood; B Odlozilik; O Willi; M Borghesi; et al. (New Journal of Physics, 2023)
Helical coil accelerators are a recent development in laser-driven ion production, acting on the intrinsically wide divergence and broadband energy spectrum of laser-accelerated protons to deliver ultra-low divergence and quasi-monoenergetic beams. The modularity of helical coil accelerators also provides the attractive prospective of multi-staging. Here we show, on a proof-of-principle basis, a two-stage configuration which allows optical tuning of the energy of the selected proton beamlet. Experimental data, corroborated by particle tracing simulations, highlights the importance of controlling precisely the beam injection. Efficient post-acceleration of the protons with an energy gain up to ∼16 MeV (∼8 MeV per stage, at an average rate of ∼1 GeV m ^−1 ) was achieved at an optimal time delay, which allows synchronisation of the selected protons with the accelerating longitudinal electric fields to be maintained through both stages.